Notch1 Signaling Regulates the Th17/Treg Immune Imbalance in Patients with Psoriasis Vulgaris - Lei Ma; HaiBo Xue; Tianqin Gao; MeiLan Gao; YuJie Zhang (Mediators of Inflammation)
Purpose. To evaluate the regulating effect of Notch1 signaling on Th17/Treg immune imbalance in psoriasis vulgaris (PV). Materials and Methods. Notch1, Hes-1, RORγt, Foxp3, IL-17, and IL-10 mRNA expression, as well as Th17 and Treg cell percentages in peripheral CD4+ T cells, were detected by real-time quantitative RT-PCR and flow cytometry, and serum concentrations of IL-17 and IL-10 were detected by ELISA in 36 PV patients and 32 healthy controls. Additionally, CD4+ T cells from 12 PV patients were treated with γ-secretase inhibitor DAPT, and the above indexes were measured. Results. PV patients presented distinct Th17/Treg immune imbalance and highly expressed Notch1 and Hes-1 mRNA levels, which were positively correlated with psoriasis area and severity index (PASI) and the ratios of Th17/Treg and RORγt/Foxp3. DAPT treatment resulted in the obvious downregulation of Th17 cell percentage in cocultured CD4+ T cells, RORγt and IL-17 mRNA levels, and IL-17 concentration in cell-free supernatant from cocultured CD4+ T cells of PV patients in a dose-dependent manner, while there was no significant influence on Treg cell percentage, Foxp3, and IL-10 expression, therefore leading to the recovery of Th17/Treg immune imbalance. Conclusion. Notch1 signaling may contribute to the pathogenesis of PV by regulating Th17/Treg immune imbalance.